2011
DOI: 10.1016/j.ijgo.2011.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide metabolite levels and assessment of cervical length in the prediction of preterm delivery among women undergoing symptomatic preterm labor

Abstract: Objective: To evaluate the diagnostic accuracy of measuring cervical length (CL) in combination with cervical and plasma nitric oxide metabolite (NOx) levels to identify women undergoing preterm labor (PTL) who will deliver preterm. Methods: A hospital-based prospective cohort study of 730 women undergoing spontaneous PTL between 24 and 33 weeks + 6 days of pregnancy was conducted. Measurement of cervical and plasma NOx levels and ultrasonographic assessment of CL were performed to find the best model to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…In other studies, there was variable cutoff. In comparison with our assessment (NOx ≤31 [μmol/L]), some studies have reported the higher amount of NO (NOx ≤ 123 [μmol/l]),[13] while other probations have stated the lower NO level compared with our findings. [18] We believe that the fluctuation of NOx level might be related to our different population nature or small sample size, and we encounter with limiting external validation of the result, and more investigations are needed to evaluate the level of NO in bigger population.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…In other studies, there was variable cutoff. In comparison with our assessment (NOx ≤31 [μmol/L]), some studies have reported the higher amount of NO (NOx ≤ 123 [μmol/l]),[13] while other probations have stated the lower NO level compared with our findings. [18] We believe that the fluctuation of NOx level might be related to our different population nature or small sample size, and we encounter with limiting external validation of the result, and more investigations are needed to evaluate the level of NO in bigger population.…”
Section: Discussioncontrasting
confidence: 60%
“…Despite finding a positive correlation between NOx level and CL in PTL, other findings reported the opposite relation. [13] The survey performed by Duckitt and Thornton demonstrated that using magnesium sulfate, which causes an elevated level of NO, had no significant effect of PTL. [25] None of the trials addressed the alteration in cervical ripening or prolonged delivery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations